2021
DOI: 10.1021/acs.jpclett.1c03286
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Properties of Oxidized Graphene: Effects of Strain and an Electric Field on Flat Bands and the Energy Gap

Abstract: A multiscale modeling and simulation approach, including first-principles calculations, ab initio molecular dynamics simulations, and a tight binding approach, is employed to study band flattening of the electronic band structure of oxidized monolayer graphene. The width of flat bands can be tuned by strain, the external electric field, and the density of functional groups and their distribution. A transition to a conducting state is found for monolayer graphene with impurities when it is subjected to an elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…The flat band is observed when the system is doped, or a strain or electric field is applied to the system. 41,42 Flat bands are energy-independent and lead to a high density of states near the Fermi energy. The band structure of 10-ASnNR in the presence of positive and negative directions of transverse electric fields is depicted in Fig.…”
Section: Band Structurementioning
confidence: 99%
“…The flat band is observed when the system is doped, or a strain or electric field is applied to the system. 41,42 Flat bands are energy-independent and lead to a high density of states near the Fermi energy. The band structure of 10-ASnNR in the presence of positive and negative directions of transverse electric fields is depicted in Fig.…”
Section: Band Structurementioning
confidence: 99%
“…There are different ways to manipulate electronic band structure and introduce a FB into 2D-materials, such as by introducing defects [14] and impurities such as hydrogen (H) [15][16][17], oxygen (O) [18,19], hydroxyl (OH) [16,18,19], fluorine (F) [17,20], and adsorption of NO molecule [21]. It was found that covalently bound impurities, such as hydroxyl groups, can induce midgap states in graphene [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, in the current study, the structural and electrical characteristics of several monolayer and bilayer combinations of pure and oxygenated graphene are examined. Although the structure of single-layer oxidized graphene with a pair of epoxy and hydroxyl functional groups has been structurally investigated in earlier studies using ab initio calculations [6], we consider it is also required to present a full investigation and provide specifics. The purpose of this research is to look at the structural geometry and electrical properties of layered graphene-based structures.…”
Section: Modelmentioning
confidence: 99%
“…The occurrence of this event around the Fermi level affects the electronic properties of materials. The stretching of the bonds in the direct lattice is typically what causes the development of intermediate gap states in the reciprocal lattice [6]. In 2D structures, the substitution of some atoms and the addition of agents by applying tension to the bands causes a change in the density and energy of electrons, and their ability to mobility in the material, and consequently a change in the energy levels.…”
Section: Introductionmentioning
confidence: 99%